2013
DOI: 10.1016/j.jep.2012.10.040
|View full text |Cite
|
Sign up to set email alerts
|

From popular use to pharmacological validation: A study of the anti-inflammatory, anti-nociceptive and healing effects of Chenopodium ambrosioides extract

Abstract: The results, including the inhibition of mediators (BK, NO, SP, PGE(2) and TNF-á) and enzyme (MPO and ADA) activity, validate the use of the plant under study for therapeutic treatment of anti-inflammatory, painful and wound healing processes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
46
1
12

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 88 publications
(60 citation statements)
references
References 39 publications
1
46
1
12
Order By: Relevance
“…The model involves the participation of several cell types and mediators [27]. The mouse pleural inflammatory response induced by carrageenan constitutes an inflammatory model characterized by two distinct phases: (1) 4 h after carrageenan injection and (2) 48 h after carrageenan injection.…”
Section: Discussionmentioning
confidence: 99%
“…The model involves the participation of several cell types and mediators [27]. The mouse pleural inflammatory response induced by carrageenan constitutes an inflammatory model characterized by two distinct phases: (1) 4 h after carrageenan injection and (2) 48 h after carrageenan injection.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Chenopodium ambrosioides occupies the 17th position on the National Register of Plants of Interest to the National Health System (Relação Nacional de Plantas de Interesse do Sistema Único de Saúde - RENISUS), a list compiled by the Brazilian Government which consists of 71 plant species used in folk medicine for the alternative treatment of health conditions [13]. Experimental studies have shown that C. ambrosioides exerts immunostimulatory [14, 15], antimicrobial [16], anti-inflammatory and antinociceptive activities [17, 18]. …”
Section: Introductionmentioning
confidence: 99%
“…These bioactive compounds generally exhibit anti-inflammatory activities, which indicate its use for preventing osteoporosis [22][23][24] .…”
Section: Discussionmentioning
confidence: 99%